Περί της καταστάσεως του κλήρου στη Σμύρνη κατά το δεύτερο ήμισυ του ΙΗ’ αιώνα - Μποροβίλος Γεώργιος Ε. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
This article presents and studies systematically for the first time a critical text on the Orthodox clergy of Smyrna during the second half of the eighteenth century. This text precedes chronologically all similar texts voicing criticism on the condition and behaviour of the clergy, that were inspired by the principles of Enlightenment. The author of the text Gregory, archdeacon to the Metropolitan of Smyrna, and later Ecumenical Patriarch Gregory V, was not motivated by secular principles in his criticism but by the patristic traditions of the Orthodox Church. The text in question is of great interest not only because it provides invaluable information about the life of the Orthodox clergy in the area, but also because it represents a critical attitude emanating from religious princi- pies, free from the acerbity and divisiveness that marks the corresponding texts of the Enlightenment. The text in question constitutes the preface to an edition of St. John Chrysostom’s Homilies on Priesthood, published in Venice in 1783.